Long-term safety and efficacy of a highly purified plant-based nutraceutical for improving clinical parameters of liver function in healthy participants: a randomized, double-blind, placebo-controlled clinical trial - Patel, Ghanashyam; Shah, Saumin; D’Adamo, Christopher R. (Frontiers in Nutrition, 2026)
BackgroundLiver function is foundational to human health. While numerous herbal extracts have individually been shown to improve liver function, there are relatively few studies on combinations of herbal ingredients that may have synergistic effects. In addition, capsule fatigue is a common problem when aiming to incorporate multiple ingredients to support liver health. With these gaps in mind, the goal of this study was to evaluate the safety and efficacy of a highly purified plant-based nutraceutical containing organic herbal extracts of turmeric, dandelion, milk thistle, and ginger on liver function parameters.MethodsA randomized, placebo-controlled clinical trial was conducted to evaluate the efficacy of this nutraceutical liquid formula. Healthy adults were randomized 1:1 to receive the nutraceutical product or placebo (both 60 mL) twice daily for 180 days. The primary endpoint was change in liver function tests (alanine aminotransferase [ALT], aspartate aminotransferase [AST], alanine phosphatase [ALP], gamma-glutamyl transferase [GGT]) from baseline to end of study. Safety was also evaluated. The primary endpoint was compared between study arms via analysis of covariance.ResultsIn total, 130 participants enrolled in the trial; 65 were randomized to each group. Mean improvements in ALT, AST, ALP, and GGT were significantly greater with the nutraceutical product than placebo (p ≤ 0.001). No adverse events were reported.DiscussionSupplementation with this liquid nutraceutical formula improved the liver enzyme profile of healthy individuals, suggesting that it may mitigate a trend toward higher liver enzyme levels over time in a convenient manner that fosters compliance.Clinical trial registrationhttps://ctri.nic.in/Clinicaltrials/login.php, CTRI/2023/06/054492.